Atuação educativa de êxito de biblioteca tutorada : uma análise de conteúdo das produções científicas entre o período de 2005 a 2015 em fontes nacionais e internacionais - Sousa, Gleicy Aparecida de (2017)
So, several questions raised from these findings: Why does the Tutored library, a learning enhancing space, it is not being implemented such as other AEEs? What elements do confirm CREA’s affirmation about the learning enhancing promoted by the Tutored Library project? How do Tutored Library work? Are there any researches about Tutored Library in Latin America? The main goal of this investigation is to identify what has been produced scientifically about Tutored Library between 2005 and 2015. Our specific goals are: characterize the AEE of the Tutored Library (functionally and organization); identify learning enhancing elements of Tutored Library within scientific productions; situate scientific productions and analyze them. This is a bibliographic study developed within a qualitative approach based on “Content analysis”. The analysis of these productions answered our questionings, anguishes and concerns. We would like to obtain more scientific productions about Tutored Library project, but it was not possible. The localized number of scientific productions did not meet our expectations, however, it motivated us to search in this scenario, to research more about the Tutored Library, to know other schools that develop AEE, to identify the contexts in which it is inserted, Other researches, so that, in this way, we appropriate an object not yet known. Another interesting point was the frequency of the recording units present in the texts analyzed. The less-mentioned registry units are among the important elements in the Tutored Library, which is the educational participation of the community and the length of class time. By breaking with the barrier that separates the surrounding community and the school, we consolidate actions and partnerships that will help all the subjects involved in this space of the school to be transformed in some way, with values, moral, scientific knowledge, literacy, reading among others Learning. In concluding the analyzes we feel the need not only to have a scientific production that unifies the productions that we find. We consider the research to be unfinished, because the initial objectives indicated the lack of accompanying the development of a Tutored Library, so that we can articulate our contribution to a meaningful experience, which may be possible as we continue the studies and research on the subject discussed, to To identify the reasons why this AEE has not been disseminated in the same way as the others.